The Role of Women’s Administrative Capabilities to Keep Pace with Strategic Transformation 2030 - Sharif, Yahya Ahmed (Journal of Economic, Administrative and Legal Sciences, 2022)
There has become an urgent need to increase and activate the participation of women in the field of educational leadership to contribute effectively to achieving the strategic transformation process in the Kingdom of Saudi Arabia. One of the most prominent goals of the 2030 Vision of the Kingdom is to contribute to increasing Saudi women’s participation in the labor market and to allow them to assume senior leadership positions. Based on the foregoing, the current study aimed to identify the role of women’s administrative capabilities in the Kingdom of Saudi Arabia to keep pace with strategic transformation 2030. To achieve the objectives of the study, the descriptive analytical method was used to prepare the study, as well as using the questionnaire as a tool for collecting data from the sample of the study population. The current study was conducted on All 44 women leaders in the El-Darb Teaching Office in the Department of Education in Sabya in Jazan during the first semester of the academic year 1441/1442 AH. After analyzing the data, a number of results were reached, most notably: There are no statistically significant differences at the significance level (α ≤ 0.05) for the role of women’s administrative capabilities to keep pace with strategic transformation 2030 attributable to the demographic variables (age, academic qualification, number of years of experience) of women leaders (the study population). According to the study results, The research made several recommendations, the most important of which are: (a) the necessity of enhancing the readiness of women’s administrative capabilities to assume leadership positions in schools in the El-Darb Teaching Office to keep pace with strategic transformation 2030, and (b) achieving compatibility between the training programs offered to women leaders and the nature of their roles and responsibilities in the El-Darb Teaching Office to help keep pace with strategic transformation 2030.
Keywords: Vision 2030; strategic transformation; women leaders